Effects of foot-stretcher angle on the drive phase in ergometer rowing - Hume, P.; Soper, C.; Joe, G.; Williams, T.; Aitchson, D.; Gunn, S. (2000)
Thirteen rowers in the New Zealand elite squad completed a series of high intensity strokes on a Concept II rowing ergometer at a set stroke rate, at pre-selected randomised foot-stretcher angles. The rowers usual preferred foot-stretcher angle was used with two 2.5° increments in both dorsi- and plantar flexion directions (i.e. a total of five foot-stretcher angles). The rowers' ankle dorsiflexion/plantar flexion was measured as flexibility of this joint may affect the force production with change in stretcher angle. All analogue data were recorded on a PC computer with LabView. A customised foot-stretcher mounted under the right foot measured the magnitude and location of the equivalent point load (Aitchison and Williams, 1999). Kinematics of the legs, back and arms in the sagittal plane were recorded using a Panasonic video camera and Video-expert II digitising system. Standard electromyography (EMG) procedures (Winter, 1990) were used for recording muscle activity of gluteus maximus, vastus lateralis, biceps femoris, gastrocnemius and tibias anterior (of the right lower limb). EMG variables were measured from smoothed data (second order Butterworth filter with a 6 Hz cut-off frequency) using customised LabView EMG data analysis software (Hume and Soper, 1999). Results showed that the foot stretcher could be optimised for each athlete in terms of force production, lower limb kinematics, muscle activation patterns, perceived exertion and perceived comfort. The second phase of the study will involve on-water testing. Comparisons will be made for different foot stretcher angles and also between ergometer rowing and on-water rowing. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)